PENGARUH MEDIA PEMBELAJARAN TEKNOLOGI AUGMENTED REALITY (AR) PADA TEMATIK TERPADU TERHADAP HASIL BELAJAR SISWA SD - Claudya, Tifanni; Sri Lena, Mai (STKIP Subang, 2021)
This research is motivated by the absence of new technology based learning media in the integrated thematic learning process. Thios studdy aims to determine the effiect of Augomented Rveality( AR) tekhnology learning media on integrated thematic on student learning outcomes in grade IV SDN 005 Langgini, Bangkinang District in the even semester of the 2020/ 2021 akademic year. This reseiarch was conducted on Theme 8 Sub- theme 2 Learning 3 and 4. The type of research was quantitative in the foarm off a quasi exsperimental design. By design Nonequivalent control group design. The samplig technique is cluster random sampling. The populations consistead of several schools located in on cluster 2 Bangkinang District and grades IV A and IV B SDN 005 Langgini werw selected as samples. Class IV A as the control claess annd claess IV B as the experimental class. Based on the results of the study, the average value of the experimental class was 80, 00 wit a standarnd deviationsf of 8, 18 and the average value of the control class was 72, 22 wih a standarnd deviatian ef 8, 17. Baseaid om the calculatiop of th t- tst obtaind tcount 3, 1966 Whil the ttableat the confidece tingkat 0, 05 is 2, 017 so tha tcounnt ttble. Thuss, it can be conclded theat there is a positive and significbant effecth of using Augmented Reality( AR) technology learning media in integrated thematic on the learnisng outwcomes of fourth graode students at SDN 005 Langgini.